A Stability Result for a Swelling Porous System with Nonlinear Boundary Dampings. (9th June 2022) - Al-Mahdi, Adel M.; Messaoudi, Salim A.; Al-Gharabli, Mohammad M.
Abstract : In this work, we consider a swelling porous system where the damping terms are on the boundary. We establish an explicit and general decay result, without imposing restrictive growth assumption near the origin on the damping terms. Our result allows a larger class of damping terms, and the usual exponential and polynomial decay estimates are only special cases. We also give some illustrative examples.